Geochemical, Mineralogical, and Geomorphological Characterization of Ash Materials as a Tracer for the Origin of Shifting Sands near Oldupai Gorge, Ngorongoro, Tanzania - Mohamed Zengo Makongoro; Maheswara Rao Vegi; Said Ali Hamad Vuai; Michael Mwita Msabi (The Scientific World Journal)
Shifting sand (SS) is a single dune-shaped mass of black ash material moving across western Ngorongoro in northern Tanzania. The moving sand has become an important tourist destination for several decades. Despite being part of the important geosites at the Ngorongoro Conservation Area, the nature, origin, and behaviors demonstrated by SS remain poorly understood. This work contributes toward understanding the nature and identification of the possible origin of the SS through the correlation of geochemical, mineralogical, and geomorphological data of ash material from four selected locations in the study area. To achieve this goal, elemental, mineralogical, and morphological characterization of ash samples was performed by energy-dispersive X-ray fluorescence, polarized petrographic microscopy, automated sieve shaker, and binocular microscopy techniques, respectively. Correlation studies were based on magnesian-ferriferous associations, similarities in mineralogy, particle size, shape, and distribution patterns of ash materials, and weather data. There are close similarities in the chemical compositions among ash samples of SS, Ootun area, and Oldoinyo Lengai. Augite and magnetite minerals appear only in samples of SS, Ootun area, and Oldoinyo Lengai, while hornblende appears only in the samples from the Ngorongoro crater. Oldoinyo Lengai rock petrography revealed significant amounts of augite minerals. Blocky and elongated-shaped ash particles dominate the samples from SS, Ootun area, and Oldoinyo Lengai. The particle size of ash materials decreases westwards across the study site. The distribution patterns of ash material align with the west-south-west wind direction. Based on these findings, the study concludes that SS and Ootun ash could be tephra depositions resulting from past volcanic eruptions of Oldoinyo Lengai.